Evaluation of preprocedural statin loading on clinical outcomes in patients undergoing elective percutaneous coronary intervention - Sinan, Umit Yasar; Keskin Meric, Bengisu; Bursa, Nurbanu; Moumin, Gkiozde; Kaya, Aysem; Arat Ozkan, Alev (Frontiers in Cardiovascular Medicine, 2024)
Background and aim High-dose statin therapy before percutaneous coronary intervention (PCI) is thought to reduce the occurrence of Peri-procedural Myocardial Infarction (PPMI), which is associated with increased mortality and prolonged hospitalization, especially in statin naïve patients. This study aims to investigate the effect of rosuvastatin loading dose on PPMI and major adverse cardiac and cerebrovascular events (MACCE) in patients undergoing elective PCI, considering their statin use. Methods One hundred sixty-five patients with stable coronary artery disease (CAD) without heart failure (HF) or chronic kidney disease (CKD) were included in the study. They were divided into two groups: patients already on statin treatment (n:126) and statin naive patients (n:39). Both groups were randomly assigned to high-dose (40 mg) rosuvastatin (n:86) or a non- loading dose group (n:79). The primary endpoint was the incidence of PPMI, and the secondary endpoint was MACCE. Results The mean age of study population was 59 ± 9.4 years with 77% being male (n = 127). The median follow-up (FU) time was 368 day. Thirty patients were diagnosed with PPMI after PCI (19 in the high-dose group and 11 in the no-loading-dose group). Meanwhile, less than half of study population (77 patients, 46.7%) had complex lesion type (B2, C) and 88 of those (53.3%) had simple lesion type (A, B1). PPMI was observed more frequently in statin-naive patients (23%) than in statin users (17%), although the difference was not statistically significant. Only two patients (1.2%) experienced MACCE during the FU period. One of these patients, who had a type C lesion, belonged to group A2 and underwent Target Vessel Revascularization (TVR) on the 391st day. The other patient, with a type B1 lesion, was in group A1 and was hospitalized due to Acute Coronary Syndrome (ACS) on the 40th day of FU. Conclusions Pre-procedural administration of high dose rosuvastatin in patients with stable coronary artery disease did not decrease PPMI, independent of chronic statin use.